RELATIONSHIP BETWEEN KNOWLEDGE AND PERCEPTION OF NURSES WITH TRIAGE SKILLS IN THE EMERGENCY ROOM (IGD) OF HOSPITALS IN PARIAMAN CITY IN 2024 - MALINI, NADIA RARA; KASMORA, DEPERMAN; MAIFITA, YESI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Nurses as health workers are required to improve their knowledge and provide maximum service in order to provide optimal service to patients, especially emergency services which can be assessed from the nurse's ability in terms of responsiveness, timely service, good attitude in providing service, concern and attention in providing service and can improve the quality of service. Nurses must improve their professionalism in implementing nursing care, as well as understand the assessment of primary and secondary surveys, carry out triage quickly and correctly. This study aims to determine the relationship between knowledge and perception of nurses with triage skills in the Emergency Room (IGD) of Hospitals in Pariaman City in 2024. This type of quantitative research uses a Cross Sectional Study approach. The study was conducted on September 13-20, 2024 in the Emergency Room (IGD) of the Hospital in Pariaman. The research sample was 33 people. Sampling by Total Sampling. Statistical test using Chi Square degree of significance (p value <α 0.05) The results of the study showed that more than half of the respondents had good knowledge, namely 26 23 (69.7%). The most respondents' perception was good perception, namely 16 (48.5%). More than half of the respondents had good triage skills, namely 25 (75.8%). Conclusion, There is a relationship between nurses' knowledge and perceptions with triage skills in the Emergency Room (IGD) of Hospitals in Pariaman City in 2024. Suggestion, This study is expected to be a guideline for nurses in improving triage skills in nurses in emergency services